Strand Corrosion in Prestressed Concrete Structures - Wang, Lei (Springer Nature, 2023)
This is an open access book. This book focuses on the durability problems of existing prestressed concrete (PC) structures caused by strand corrosion, clarifies the mechanical behavior of corroded prestressing strands, corrosion-induced cracking, bond degradation, prestress loss and structural performance deterioration, and proposes the corresponding prediction models. Its aim is to provide the knowledge, tools, and methods to understand the deterioration phenomena of PC structures. We hope that this text may be useful for those who work in the field of civil engineering. It is suitable for teachers and students majoring in civil engineering in universities, and researchers in the field of civil engineering. It is also suitable for practitioners of design institutes, construction units, supervising units and traffic management departments.